Chronologic constraints on hominin dispersal outside Africa since 2.48 Ma from the Zarqa Valley, Jordan. (1st September 2019) - Scardia, Giancarlo; Parenti, Fabio; Miggins, Daniel P.; Gerdes, Axel; Araujo, Astolfo G.M.; Neves, Walter A.
Abstract: Recent discoveries constrain the presence of hominins in North Africa since ca. 2.4 Ma and in China since ca. 2.1 Ma, providing a new temporal framework for the earliest migration out of Africa. No Paleolithic sites of such age exist in the Levant, the natural corridor between Africa and Asia. The Dawqara Formation in the Zarqa Valley, Jordan, has been known since the early 1980s because of the presence of artifacts at different stratigraphic levels within its fluvial sediments, consisting of choppers, cores, and flakes. Although most of the artifacts display signs of transport, they bear unambiguous evidence of manufacture, and document hominin presence in the Zarqa Valley during the deposition of Dawqara Formation. Based on integrated chronology provided by paleomagnetic, 40 Ar/ 39 Ar, and U-Pb dating methods, our study shows that the Dawqara Formation was deposited between 2.52 ± 0.01 Ma and the Matuyama–Olduvai geomagnetic reversal (1.95 Ma). By linear interpolation, the artifact-bearing stratigraphic levels within the Dawqara Formation have ages of ca. 2.48 Ma, 2.24 Ma, 2.16 Ma, 2.06 Ma, and 1.95 Ma, respectively, possibly documenting continuous hominin presence in the Zarqa Valley. These new ages for the Dawqara assemblage constrain the earliest hominin dispersal out of Africa to the beginning of the Pleistocene, and pre-date by ca. 300 kyr the hominin occupation of Chinese Loess Plateau. Highlights: The Levant is a key area to investigate the exit of hominins out of Africa. The Zarqa Valley, Jordan, yielded Oldowan tools and mammal fossils from Dawqara Fm. New chronologic constraints were derived from surveys and dating methods. Constrained to 2.5–2.0 Ma, the Dawqara tools document the earliest hominin presence out of Africa.